Pengembangan Metode Isolasi Kondroitin Sulfat dari Tulang Rawan Sotong (Sepia phraonis), Pari (Raja sp.), Dan Hiu (Carcharinus falciformes) [The Isolation Development of Chondroitin Sulphate from Cuttlebone (Sepia phraonis), Ray's Cartilage (Raja sp.), and Shark (Carcharinus falciformes) ] - Moch. Amin Alamsjah; Dimas Hanindika; Noor Erma Sugijanto (Faculty of Fisheries and Marine Universitas Airlangga, 2014)
Abstract Chondroitin sulfate are drugs for osteoarthritis which usually made from pig cartilage and shark , the material can not be accepted because of the prohibition of pork and rare of shark. This study developed a method of Nakano, Garnjanagoonchorn, and Volpi . Extraction and isolation of chondroitin sulfate from alternative raw materials such as the rays and cuttlefish cartilage materials because both are abundant and cheap. Isolation results were analyzed using Fourier Transform - Infrared and Thermal Analysis diffrential, obtained 2.37% chondroitin sulfate from shark cartilage, 1.57 % from ray's, while the squid was not obtained chondroitin sulfate.